2006
DOI: 10.1007/s00213-006-0496-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential neurochemical and behavioral adaptation to cocaine after response contingent and noncontingent exposure in the rat

Abstract: Response-noncontingent cocaine administration is particularly prone, compared to response-contingent administration, to induce behavioral and biochemical sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
98
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 46 publications
12
98
2
1
Order By: Relevance
“…Indeed, neurobiological correlates of reward (eg neurotransmitter release in the basal ganglia) are increased after response-contingent drug infusions by a far greater magnitude than by response non-contingent drug infusions (Wilson et al, 1994;Mark et al, 1999;Kimmel et al, 2005;Lecca et al, 2007). In addition, different gene expression, neurochemical, stress system, and behavioral adaptations occur in response to volitional vs nonvolitional drug consumption (Stefanski et al, 1999;Jacobs et al, 2005).…”
Section: Reward-enhancing and Reinforcing Effects Of Nicotine Requirementioning
confidence: 99%
“…Indeed, neurobiological correlates of reward (eg neurotransmitter release in the basal ganglia) are increased after response-contingent drug infusions by a far greater magnitude than by response non-contingent drug infusions (Wilson et al, 1994;Mark et al, 1999;Kimmel et al, 2005;Lecca et al, 2007). In addition, different gene expression, neurochemical, stress system, and behavioral adaptations occur in response to volitional vs nonvolitional drug consumption (Stefanski et al, 1999;Jacobs et al, 2005).…”
Section: Reward-enhancing and Reinforcing Effects Of Nicotine Requirementioning
confidence: 99%
“…The DA response to a natural reward does not generally persist over time, as the organism rapidly habituates to these stimuli after a few exposures. Conversely, the response to addictive drugs is not influenced by habituation, as each drug administration stimulates the release of DA (Bradberry et al, 2000;Di Chiara et al, 2004;Lecca et al, 2007). In addition, the DA response of addictive substances is several fold higher than that elicited by novel, naturally occurring rewards .…”
Section: Mesostriatal Acetylcholine and Reward Mediationmentioning
confidence: 99%
“…Microdialysis studies, in addition, have shown that cocaine increases extracellular DA in the NAc even after i.v. self-administration (Di Ciano et al, 1995;Justice, 1989, 1991;Wise et al, 1995;Lecca et al, 2007a). Moreover, preferential stimulation of DA transmission in the ventral striatum by amphetamine has been demonstrated in humans by Positron Emission Tomography of [ 11 C] raclopride binding (Drevets et al,1999(Drevets et al, , 2001Leyton et al, 2002;Martinez et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This preferential action has been initially documented by microdialysis studies in acutely experimenter-administered rats (Aragona et al, 2008;Pontieri et al, 1995) and later demonstrated in rats during acquisition of i.v. cocaine SA (Lecca et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%